The investigation of sudden arrhythmic death syndrome (SADS)—the current approach to family screening and the future role of genomics and stem cell technology - Vyas, Vishal; Lambiase, Pier (Frontiers in Physiology, 2013)
SADS is defined as sudden death under the age of 40 years old in the absence of structural heart disease. Family screening studies are able to identify a cause in up to 50% of cases-most commonly long QT syndrome, Brugada and early repolarisation syndrome, and catecholaminergic polymorphic ventricular tachycardia using standard clinical screening investigations including pharmacological challenge testing. These diagnoses may be supported by genetic testing which can aid cascade screening and may help guide management. In the current era it is possible to undertake molecular autopsy provided suitable samples of DNA can be obtained from the proband. With the evolution of rapid sequencing techniques it is possible to sequence the whole exome for candidate genes. This major advance offers the opportunity to identify novel causes of lethal arrhythmia but also poses the challenge of managing the volume of data generated and evaluating variants of unknown significance. The emergence of induced pluripotent stem cell technology could enable evaluation of the electrophysiological relevance of specific ion channel mutations in the proband or their relatives and will potentially enable screening of idiopathic ventricular fibrillation survivors combining genetic and electrophysiological studies in derived myocytes. This also could facilitate the assessment of personalised preventative pharmacological therapies. This review will evaluate the current screening strategies in SADS families, the role of molecular autopsy and genetic testing and the potential applications of molecular and cellular diagnostic strategies on the horizon.